2014
DOI: 10.1007/s11356-014-3332-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fate and exposure; neonicotinoids and fipronil

Abstract: Systemic insecticides are applied to plants using a wide variety of methods, ranging from foliar sprays to seed treatments and soil drenches. Neonicotinoids and fipronil are among the most widely used pesticides in the world. Their popularity is largely due to their high toxicity to invertebrates, the ease and flexibility with which they can be applied, their long persistence, and their systemic nature, which ensures that they spread to all parts of the target crop. However, these properties also increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
783
4
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,091 publications
(834 citation statements)
references
References 168 publications
24
783
4
23
Order By: Relevance
“…The concentration used was chosen to reflect field-realistic values. Reported values of the maximum amounts of clothianidin residues found in the nectar of treated crops vary from 1 to 14 ppb with the average values ranging from 0.3 to 5.4 ppb [29,[37][38][39]. Fresh sugar water solutions (contaminated with clothianidin or not) were renewed every 2 -4 days, and the amount of sugar water collected was recorded by weighting the feeders.…”
Section: Materials and Methods (A) Bees And Treatmentsmentioning
confidence: 99%
“…The concentration used was chosen to reflect field-realistic values. Reported values of the maximum amounts of clothianidin residues found in the nectar of treated crops vary from 1 to 14 ppb with the average values ranging from 0.3 to 5.4 ppb [29,[37][38][39]. Fresh sugar water solutions (contaminated with clothianidin or not) were renewed every 2 -4 days, and the amount of sugar water collected was recorded by weighting the feeders.…”
Section: Materials and Methods (A) Bees And Treatmentsmentioning
confidence: 99%
“…When temperature reach to 20 ºC, the rate of imidacloprid solubility in water increase 610 higher than other circumstances with aqueous photolysis reach to 0.2 faster and water-sediment reach to 129 slower than other condition, this also explain the reason for disappear imidacloprid from November samples [66].…”
Section: Discussion Of Gc/ms Resultsmentioning
confidence: 96%
“…So before the targeted plants harvested, the concentration of pesticide reduced to half the concentration when it apply to plant, that is another reason of disappearing oxamyl and imidacloprid active ingredients in all samples. According to reference [64], imidacloprid can bind with soil organic matter and that reduce potentially the ability of imidacloprid for leaching throw the soil, this explain the reason of high ability for decomposers for degrade the active ingredients of imidacloprid. The samples 29/8/2016, zucchini from Sulaimaniyah and 24/8/2016, eggplant from Al-Yusufiyah, showed no pesticide residues or pesticide bi-products residues, the investigation revealed that the kind of planting soil is sandy soil.…”
Section: Discussion Of Gc/ms Resultsmentioning
confidence: 99%
“…Neonicotinoids are persistent in soil and water, remain in the environment for a long time, and spread quickly through surface water (Bonmatin et al 2015). Through systemic uptake it also contaminates wild flowers (Botías et al 2015).…”
Section: Large-scale Prophylactic Use Of Systemic Neonicotinoid Insecmentioning
confidence: 99%